Based on network pharmacology and molecular docking to explore the protective effect of Epimedii Folium extract on cisplatin-induced intestinal injury in mice - Xia, Juan; Hu, Jun-Nan; Wang, Zi; Cai, En-Bo; Ren, Shen; Wang, Ying-Ping; Lei, Xiu-Juan; Li, Wei (Frontiers in Pharmacology, 2022)
Abstract Background: Epimedii Folium, as a natural botanical medicine, has been reported to have protective effects on intestinal diseases by modulating multiple signaling pathways. This study aimed to explore the potential targets and molecular mechanisms of Epimedii Folium extract (EFE) against cisplatin-induced intestinal injury through network pharmacology, molecular docking, and animal experiments. Methods: Network pharmacology was used to predict potential candidate targets and related signaling pathways. Molecular docking was used to simulate the interactions between significant potential candidate targets and active components. For experimental validation, mice were intraperitoneally injected with cisplatin 20 mg/kg to establish an intestinal injury model. EFE (100, 200 mg/kg) was administered to mice by gavage for 10 days. The protective effect of EFE on intestinal injury was analyzed through biochemical index detection, histopathological staining, and western blotting. Results: Network pharmacology analysis revealed that PI3K-Akt and apoptosis signaling pathways were thought to play critical roles in EFE treatment of the intestinal injury. Molecular docking results showed that the active constituents of Epimedii Folium, including Icariin, Epimedin A, Epimedin B, and Epimedin C, stably docked with the core AKT1, p53, TNF-α, and NF-κB. In verified experiments, EFE could protect the antioxidant defense system by increasing the levels of glutathione peroxidase (GSH-Px) and catalase (CAT) while reducing the content of malondialdehyde (MDA). EFE could also inhibit the expression of NF-κB and the secretion of inflammatory factors, including TNF-α, IL-1β, and IL-6, thereby relieving the inflammatory damage. Further mechanism studies confirmed that EFE had an excellent protective effect on cisplatin-induced intestinal injury by regulating PI3K-Akt, caspase, and NF-κB signaling pathways. Conclusion: In summary, EFE could mitigate cisplatin-induced intestinal damage by modulating oxidative stress, inflammation, and apoptosis.